Ecoengineering Solutions for the Impairment of Spreading and Growth of Invasive Spartina patens in Mediterranean Salt Marshes - Cruz de Carvalho, Ricardo; Feijão, Eduardo; Duarte, Irina; Pinto, Vanessa; Silva, Marisa; Matos, Ana Rita; da Silva, Anabela Bernardes; Caçador, Isabel; Reis-Santos, Patrick; Fonseca, Vanessa F.; Duarte, Bernardo (Frontiers in Marine Science, 2021)
The invasion of natural communities by non-indigenous species represents one of the most serious threats to biodiversity. Understanding the ecophysiology of invasive species can provide insights into potential physiological handicaps relative to native species. By doing so, we can leverage the development of ecoengineering solutions for the removal of non-indigenous species, preferably using non-chemical methods. Spartina patens is a known invasive species of cordgrass aggressively proliferating in Mediterranean salt marshes, producing impenetrable monospecific stands. As its occurrence is delimited by the upper high tide water level, we hypothesized that S. patens is intolerant to waterlogging. Therefore, we developed a field experiment where strands of S. patens were kept waterlogged over the entire tidal cycle for 30 days. At the end of the experimental period, plants in the trial plots exhibited severe stress symptoms at different physiological levels compared with control plots (no intervention). At the photobiological level, intervened plants exhibited lower efficiency in producing chemical energy from light, whilst at the biochemical level waterlogging impaired the antioxidant system and increased lipid peroxidation products. Furthermore, the application of chlorophyll a pulse amplitude modulated (PAM) fluorometry, a non-invasive technique, allowed us to evaluate the effectiveness of the implemented measures, being the tool that provided the best separation between the control and intervened population. Considering the physiological traits observed here, ecoengineering solutions based on increased waterlogging of S. patens stands, can be a low-cost and efficient measure to reduce the spreading and growth of this invasive species in the Mediterranean and other salt marshes worldwide with little disturbance.